ACTR-32. NRG ONCOLOGY RTOG 1205: RANDOMIZED PHASE II TRIAL OF CONCURRENT BEVACIZUMAB AND RE-IRRADIATION VS. BEVACIZUMAB ALONE AS TREATMENT FOR RECURRENT GLIOBLASTOMA. (11th November 2019) - Tsien, Christina; Pugh, Stephanie; Dicker, adam; Raizer, Jeffrey; Matuszak, Martha; Lallana, Enrico; Huang, Jiayi; algan, ozer; Taylor, Nicholas; Portelance, Lorraine; Villano, John; T Hamm, John; et al.
Abstract: This study sought to determine whether re-irradiation (ReRT) and concurrent bevacizumab (BEV) improves overall survival (OS) compared to BEV alone in recurrent glioblastoma (GBM). Patients (pts) were randomized 1:1 to ReRT (35 Gy/10 fractions) plus BEV (IV 10 mg/kg q2 wks) vs. BEV alone. With 160 pts, there was 80% power to detect a 31% reduction in death hazard for BEV+RT at a one-sided significance level of 0.10 using a log rank test. OS and PFS were estimated by Kaplan-Meier and HRs estimated by exact binomial distribution. Objective response was assessed using MacDonald and RANO criteria. From 11/2012 to 4/2016, 182 pts were randomized, with 170 eligible, analyzable pts. 11 pts did not receive protocol treatment. Patient characteristics (age, KPS, re-resection rates) were balanced between arms. Median f/u for censored pts was 12.8 months (mos; min-max, 0.03–52.8). BEV+ReRT did not improve OS vs BEV alone, with median OS of 10.1 vs 9.7 mos, (HR=0.98, 95% CI=0.70–1.38, p=0.46). Median PFS for BEV+RT and BEV was 7.1 vs. 3.8 mos, respectively (HR=0.73, 95% CI=0.53–1.0, p=0.051). BEV+ReRT improved 6-mo PFS rate (PFS6): 54 vs. 29%, (HR=0.42, 95% CI=0.34–0.5, p=0.001). Overall, treatment was well tolerated: 5% acute and 0% delayed grade 3+ treatment-related AE. Most patients died from recurrent GBM. CONCLUSION: RTOG 1205 is the first, prospective, randomized multi-institutional study to evaluate the safety and efficacy of ReRT in recurrent GBM using modern RT techniques. Overall, ReRT was shown to be safe and well tolerated. BEV+ReRT did not demonstrate a benefit in OS but an improved PFS6, and clinically meaningful PFS improvement. Molecular correlates of response analyses are ongoing. Funded by U10CA180868, U10CA180822 from the National Cancer Institute.